Quantification of α phase strengthening in titanium alloys: Crystal plasticity model incorporating α/β heterointerfaces. (November 2022) - Zhang, Mengqi; Li, Jinshan; Tang, Bin; Wang, William Yi; Li, Kaidi; Zhang, Tianlong; Wang, Dong; Kou, Hongchao
Highlights: A strategy to quantify α phase strengthening in titanium alloys is proposed. The interface-affected zone arising from spherical primary α grains is introduced. Elastic interaction energy coupling by the semi-coherent interfaces of lamellae. The orientation and growth direction affect the non-uniform strain in α lamellae. Abstract: A strategy to quantify the second phase strengthening of α precipitates in titanium alloys is proposed to predict the mechanical performance through crystal plasticity finite element (CPFE) models. Considering the different dominant features of equiaxed and lamellar microstructures, statistical and microstructural factors are introduced to describe the slip resistance variations in the β matrix. The significant contribution of the interfaces is incorporated by introducing the interface-affected zone (IAZ) into crystal plasticity constitutive laws of equiaxed microstructures. In particular, the slip resistance variation is derived accounting for the interfacial energy distribution inside the IAZ. Meanwhile, the arrangement of the α lamellae is more compact and complex than that of spherical α grains in equiaxed microstructures; thus, instead of the IAZ, the interface length density is applied to describe the strengthening effects of the interfaces in lamellar microstructures. The elastic interaction energy induced by the semi-coherent interfaces of lamellae is obtained according to the micro-elastic theory. Using the advantages of the aforementioned improved models, CPFE simulations of the tensile behavior of equiaxed and lamellar microstructures at room temperature are performed, with the results matching well with the experimental data. Moreover, differences regarding the lattice structures and grain orientations lead to non-uniform strain partitioning in equiaxed and lamellar microstructures. Equiaxed α grains that favor prismatic slip tend to bear more plastic deformation than those favoring basal slip. The growth direction of α lamellae affects the deformation ability as well. Consequently, the proposed approach can precisely predict the mechanical properties of dual-phase titanium alloys through statistical values of microstructural features, and can be utilized in the investigations of other metals with similar structural characteristics. Graphical abstract: Image, graphical abstract